Optimal topology design for virtual networks - Youssef, Mina Nabil (Kansas State University, 2008)
Recently, virtualization was proposed in many scientific fields. Virtualization is widely applied in telecommunications where networks are required to be extremely flexible to meet the current and the unpredictable future requirements. The creation of a virtual network over the physical network allows the application developers to design new services provided to the users without modifying the underlay resources. The creation of a virtual network of light paths and light trees over the optical network allows the resources managers to utilize the huge optical capacity more efficiently. In this thesis, we consider the optimal topology design for the virtual networks taking into consideration traffic demands and quality of service constraints of the applications. Considered examples of virtual networks are the overlay networks at the application layer and the virtual light path and light tree networks at the optical layer. In the design of overlay topologies, the performance of the virtual networks is affected by traffic characteristic, and behavior of nodes which can be selfish or cooperative. Both the static and dynamic traffic demand scenarios are considered. The static demand scenario follows well known probability distributions, while in the dynamic traffic scenario, the traffic matrix is predicted through measurements over each link in the network. We study the problem of finding the overlay topology that minimizes a cost function which takes into account the overlay link creation cost and the routing cost. We formulate the problem as an Integer Linear Programming and propose heuristics to find near-optimal overlay topologies with a reduced complexity. Virtual optical networks are designed to support many applications. Multicast sessions are an example of the applications running over the optical network. The main objective in creating the hybrid topology, composed by light paths and light trees, is to increase number of supported multicast sessions through sharing the network resources. The problem of establishing the hybrid topology is formulated using the Integer Linear Programming. Extensive data results and analysis are performed on the generated hybrid topologies for evaluation.
Keywords: Computer Networks; Overlay Networks; Optical Networks; Virtual Networks; Topology Design; Topological metrics; Engineering, Electronics and Electrical (0544)